Quality of life of patients with mild hypertension treated with captopril a randomized double-blind placebo-controlled clinical trials - Yu, Hu
OBJECTIVE; To determine the quality of life (QOL) of mild hypertensive patients treated with captopril as compared to placebo. DESIGN: A randomized, double-blind, placebo-controlled clinical trial. SETTING: Out-patient clinic of Zhong Shan Hospital, a tertiary hospital in Shanghai, China. PARTICIPANTS: Adult patients aged from 18 to 79 years old with mild hypertension defined as diastolic blood pressure from 90 to 105 mmHg. There were 278 patients who were eligible to the study and only 13 were lost to follow-up. INTERVENTION: Patients were randomized to receive captopril 25 to 50 mg bid or placebo for 12 weeks. MAIN OUTCOME MEASURES: Change of QOL was compared both quantitatively and qualitatively between captopril and placebo group. Change of blood pressure and side effects were also compared. RESULTS: With intention-to-treat analysis, significantly more patients with captopril treatment improved QOL qualitatively (45.3% vs. 23.7%, p=0.0002 for physical health domain; 48.9% vs. 26.6%, p=0.0002 for mental health domain, and 33.8% vs. 11.5%, p=0.0001 for general functioning domain respectively). Quantitatively, the change of score for physical health, mental health, general functioning and the total QOL were significantly higher in the captoptril group than that in placebo group (3.01 vs. 2.23, p=0.0435; 3.18 vs. 1.32, p=0.0004; 1.65 vs. 0.64, p=0.0008; 7.84 vs. 4.19, p=0.0025). Only the p value of the physical health domain is of borderline statistical significance. Blood pressure was lowered significantly more by captopril than by placebo (16.27 vs. 7.74, p=0.000 for SBP; 13.07 vs. 6.00, p=0.000 for DBP). CONCLUSION: Compared to the placebo, captopril is not only effective in lowering blood pressure, as has been established, but is also effective in improving QOL in mild hypertensive patients.
Theses--(Master in Science in epidemiology-Clnical Epidemiology) UPCM
Keywords: Hypertension; Quality of Life; Captopril